Success and safety of high infliximab trough levels in inflammatory bowel disease. (3rd August 2018) - Drobne, David; Kurent, Tina; Golob, Sasa; Svegl, Polona; Rajar, Polona; Terzic, Sara; Kozelj, Matic; Novak, Gregor; Smrekar, Natasa; Plut, Samo; Sever, Nejc; Strnisa, Luka; et al.
Abstract: Objective: A prospective trial suggests target infliximab trough levels of 3–7 μg/mL, yet data on additional therapeutic benefits and safety of higher trough levels are scarce. Aim: To explore whether high infliximab trough levels (≥7 μg/mL) are more effective and still safe. Material and methods: In this cohort study of 183 patients (109 Crohn's disease and 74 ulcerative colitis) on infliximab maintenance treatment at a tertiary referral center we correlated fecal calprotectin and C-reactive protein to trough levels (426 samples) at different time points during treatment. Rates of infections were compared in quadrimesters (four-month periods) with high trough levels to quadrimesters with trough levels <7 μg/mL during 420 patient-years. Results: Fecal calprotectin and C-reactive protein (median [interquartile range]) were lower in patients with high trough levels (fecal calprotectin 66 mg/kg [30–257]; C-reactive protein 3 mg/L [3–3]) compared to trough levels below 7 μg/mL (fecal calprotectin 155 mg/kg [72–474]; C-reactive protein 3 mg/L [3–14.5]) ( p  < .001). High trough levels were superior also after excluding samples with trough levels <3 μg/mL from analysis. No differences in rates of infections were observed in quadrimesters with high trough levels (16/129 [12.4%]) compared to quadrimesters with trough levels <7 μg/mL (32/344 [9.3%]) ( p  = .32). Maintaining high trough levels resulted in 32% (interquartile range: 2–54%) increase of infliximab consumption. Conclusion: High infliximab trough levels provide better control of inflammation in inflammatory bowel disease without increasing the risk of infection.